Local field potentials reveal a distinctive neural signature of cluster headache in the hypothalamus - Brittain, J; Green, A; Jenkinson, N; Ray, N; Holland, P; Stein, J; Aziz, T; Davies, P (2009)
Cluster headache (CH) is a debilitating neurovascular condition characterized by severe unilateral periorbital head pain. Deep brain stimulation of the posterior hypothalamus has shown potential in alleviating CH in its most severe, chronic form. During surgical implantation of stimulating macroelectrodes for cluster head pain, one of our patients suffered a CH attack. During the attack local field potentials displayed a significant increase in power of approximately 20 Hz. To the authors' knowledge, this is the first recorded account of neuronal activity observed during a cluster attack. Our results both support and extend the current literature, which has long implicated hypothalamic activation as key to CH generation, predominantly through indirect haemodynamic neuroimaging techniques. Our findings reveal a potential locus in CH neurogenesis and a potential rationale for efficacious stimulator titration. © 2009 Blackwell Publishing Ltd.